2012
DOI: 10.1002/ptr.4897
|View full text |Cite
|
Sign up to set email alerts
|

Coriander (Coriandrum sativum L.): A Potential Source of High‐Value Components for Functional Foods and Nutraceuticals‐ A Review

Abstract: Coriander (Coriandrum sativum L.), a herbal plant, belonging to the family Apiceae, is valued for its culinary and medicinal uses. All parts of this herb are in use as flavoring agent and/or as traditional remedies for the treatment of different disorders in the folk medicine systems of different civilizations. The plant is a potential source of lipids (rich in petroselinic acid) and an essential oil (high in linalool) isolated from the seeds and the aerial parts. Due to the presence of a multitude of bioactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
171
0
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(190 citation statements)
references
References 104 publications
(160 reference statements)
4
171
0
15
Order By: Relevance
“…It is widely used in baked foods, condiments, and as a fundamental ingredient in curry mixes, creams, detergents, lotions and perfumes (Burdock & Carabin 2009;Sahib et al 2013). It has also been demonstrated that coriander leaves and seeds, their extracts and essential oils show antimicrobial, antioxidant and anti-diabetic activities (Sahib et al 2013).…”
Section: Sedative Effect Of Central Administration Of Coriandrum Satimentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely used in baked foods, condiments, and as a fundamental ingredient in curry mixes, creams, detergents, lotions and perfumes (Burdock & Carabin 2009;Sahib et al 2013). It has also been demonstrated that coriander leaves and seeds, their extracts and essential oils show antimicrobial, antioxidant and anti-diabetic activities (Sahib et al 2013).…”
Section: Sedative Effect Of Central Administration Of Coriandrum Satimentioning
confidence: 99%
“…All parts of this herb are in use as flavouring agents and/or as traditional remedies for the treatment of different disorders in the folk medicine systems (Sahib et al 2013;Zheljazkov et al 2014). In Persian traditional medicine, it has been used for the relief of anxiety and insomnia, the powdered dried seeds of coriander are given in a formulation to the treatment of children with frightening during sleep and awakening (Ahmad 2013).…”
mentioning
confidence: 99%
“…Its leaves and seeds are commonly used in south Asian, Chinese, Thai and Mexican cuisines. It also has medicinal properties -rich source of vitamins, detoxification ability by removal of heavy metals from the body and the essential oil has antibacterial property [8][9][10]. Eggplant on the other hand is one of the most commonly grown vegetable crop in India which is grown throughout the year, with an average productivity of 16.3 MT/ha, contributing to 27% of the global production.…”
Section: Introductionmentioning
confidence: 99%
“…It is also used against stomachache. Extracts from seeds of C. sativum have several pharmacological effects such as anti-fertility, antidiabetic, anti hyperlipidemic, antioxidant, and hypotensive activities (Asgarpanah and Kazemivash 2012;Sahib et al 2013). In some countries, it is traditionally used for treatment of ascariasis and hepatitis in human (Eguale et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Taniguchi et al (1996) isolated three isocoumarins, coriandrones C-E, from whole plants of C. sativum. Two types of 2-C-methyl d-erythritol glycosides were also recently isolated from the seed of C. sativum (Sahib et al 2013). The objective of the current study was therefore to assess the in vitro and in vivo anthelmintic potential of the seeds of C. sativum on H. nana.…”
Section: Introductionmentioning
confidence: 99%